Silver Based Therapies in the Management of Chronic Wounds: An Uptdate on Its Current Uses - Cristian Tineo; Cinthia M Nuñez; Ouel Sosa; Dahiana Pichardo; Juan Luis Hernández; Gustavo Collado (Achievements and Challenges of Medicine and Medical Science Vol. 9, 2024)
Background: Chronic wounds are a health problem of great magnitude around the world. Many drugs and dressings have been used in their treatment. Silver sulfadiazine (SSD) and silver nanocrystals (SNC) are among the most used particles to treat this condition. Purpose: Between 2014 and 2016, a study was conducted to compare the effectiveness of SSD and SNC regarding the wound granulation rate, treatment time, antibiotic effect, and treatment cost and to determine the frequency of these lesions in participants of the research. On this occasion, a review of this topic was arranged to find out if there is any additional information with regard to the difference between SNC and SSD for the treatment of chronic wounds and how those new findings relate to the original investigation. Methods: In the original research, data was collected from 50 patients with soft tissue lesions in the Regional University Hospital José María Cabral y Báez (HRUJMCB), in Santiago, Dominican Republic. This study was approved by the bioethics committee of the Pontifical Catholic University Madre and Maestra (PUCMM) and the HRUJMCB. Patients were followed up from August 2015 to February 2016. SPSS Statistics program was used to calculate Chi-square and assess statistical significance. This time, the comparison of some new investigations was presented with the findings of the previous study to determine how this field of chronic wounds has evolved several years later. Results: Fifty patients were included in this study, of whom 56% had diabetic foot ulcers, 22% had vascular ulcers, and 22% had pressure ulcers. In total, 42% of the patients were treated with SSD and 58% with SNC. The granulation rate was 71.4% for SSD and 89.6% for SNC, and the positive antibiotic effect was 15.9% for SSD and 25.9% for SNC. A total of 14.4% of patients treated with SSD ended their participation in the research between 8 and 14 days, 37.9% in 15–21 days, and 42.8% in \(\)21 days. For SNC, 3.4% of patients concluded their participation in 0–7 days, 34.4% in 8–14 days, 37.9% in 15–21 days, and 24.1% in \(\)21 days. The distribution of economic costs in the SSD group was as follows: USD0–22, 42.9%, and USD22–66, 57.2%, while in the SNC group, the distribution was as follows: USD0–22, 48.2%; USD22–66, 48.3%; and USD66–110, 3.4%. Conclusion: There was no statistical significance in the results of the original study; however, in percentage, SNC was superior regarding the rate of wound granulation, antibiotic effect, and healing time. The economic cost for both was similar. After reviewing new investigations in this field, there is still not enough research comparing both SSD and SNC, therefore, we suggest more investigations continue to be needed regarding these treatments to better establish their differences in granulation rates, healing times, antibiotic effects and economic costs.